فقہ الجنایات میں سقوطِ سزا کے اسباب میں فقہاء کرام کے اختلافات کا تحقیقی جائزہ: The jurisprudential differences of the jurists in the causes of the fall of punishment: A research review - Altafur Rehman; Hussain Ahmad (Al Manhal Research Journal, 2024)
According to the Islamic Shari'ah, the criminal is given a fixed punishment for the crime, if he repeats it, the punishment will be severe and if he becomes a habitual crime, he will be killed or imprisoned forever. In this way the society will be protected from its evil. But there are different reasons for the end of some punishments, but there is no such general reason that can cause the fall of every punishment in general, but different reasons have different effects on the punishments, there are some reasons that often Most of the punishments are suspended, and there are some that are less severe and some reasons are specific to certain punishments. All of them will be mentioned in the article under review.